2017
DOI: 10.1038/s41598-017-03842-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of initial active engagement in self-monitoring with a telemonitoring device on glycemic control among patients with type 2 diabetes

Abstract: This study aimed to investigate the effect of patient engagement in self-monitoring with a telemonitoring device on glycemic control among patients with type 2 diabetes. We conducted a subanalysis of the telemonitoring device study in Kaiser Permanente Northern California members. We divided the telemonitoring group into 53 frequent and 54 infrequent users based on self-monitoring of blood glucose (SMBG) frequency of the first 6 weeks. The frequency of SMBG transmitted from the telemonitoring device was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…All the trials had a high risk of performance bias, as it was infeasible to blind the participants to the intervention. Three studies did not adequately show attrition bias and reporting bias. Two studies with industry funding were selected as high risk of “other bias.”…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…All the trials had a high risk of performance bias, as it was infeasible to blind the participants to the intervention. Three studies did not adequately show attrition bias and reporting bias. Two studies with industry funding were selected as high risk of “other bias.”…”
Section: Resultsmentioning
confidence: 93%
“…Several systematic reviews and meta‐analyses have explored the effects of SMBG on glycaemic control in non‐insulin‐treated T2D patients, showing a reduction of glycated haemoglobin A1c (HbA1c) from 0.21% to 0.34% and a slight improvement in body mass index (BMI) . Despite the improvement in glycaemic control and BMI, finger pricking‐associated pain remains a burden of diabetes management .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature that does converge on specific diseases like diabetes and chronic kidney disease (CKD) only concentrate on one type of e-health technology at a time. [31,32] Evidence is limited that concentrates on the broad use of technology in addressing CVD specifically. [33] There is also lack of studies on differences in preference for using information exchange technologies between chronic and non-chronic disease patients and factors affecting these differences.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that information exchange via various portals and mobile intervention has led to increased adherence to healthy lifestyle programs, treatment regimens and disease prevention programs. [12][13][14]16,32] However, the literature on this topic is very general and seldom concentrates on different chronic diseases and conditions. Literature that does converge on specific diseases like diabetes and chronic kidney disease (CKD) only concentrate on one type of e-health technology at a time.…”
Section: Introductionmentioning
confidence: 99%